Dexamethasone is a dose-dependent perpetrator of drug–drug interactions: implications for use in people living with HIV. (17th November 2021) - Jacobs, Tom G; Marzolini, Catia; Back, David J; Burger, David M
Abstract: Global use of dexamethasone in COVID-19 patients has revealed a poor understanding of the drug–drug interaction (DDI) potential of dexamethasone, particularly with antiretroviral agents (ARVs). Dexamethasone is both a substrate and a dose-dependent inducer of cytochrome P450 3A4 (CYP3A4). As many ARVs are substrates and/or inhibitors or inducers of CYP3A4, there is concern about DDIs with dexamethasone either as a perpetrator or a victim. Assessment of DDIs that involve dexamethasone is complex as dexamethasone is used at a range of daily doses (generally 0.5 up to 40 mg) and a treatment course can be short, long, or intermittent. Moreover, DDIs with dexamethasone have been evaluated only for a limited number of drugs. Here, we summarize the available in vitro and in vivo data on the interaction potential of dexamethasone and provide recommendations for the management of DDIs with ARVs, considering various dexamethasone dosages and treatment durations.